Immunomodulation of Macrophages in Diabetic Wound Individuals by Structurally Diverse Bioactive Phytochemicals - Krishnendu Adhikary; Riya Sarkar; Sriparna Maity; Ishani Sadhukhan; Riya Sarkar; Krishnendu Ganguly; Saurav Barman; Rajkumar Maiti; Sanjoy Chakraborty; Tandra R. Chakraborty; Debasis Bagchi; Pradipta Banerjee (MDPI AG, 2024)
Diabetes-related ulcers and slow-healing wounds pose a significant health risk to individuals due to their uncertain causes. Mortality rates for diabetes foot ulcers (DFUs) range from 10% after 16 months to 24% after five years. The use of bioactive phytochemicals can play a key role in healing wounds in a predictable time. Recent literature has demonstrated that various natural substances, including flavonoids, saponins, phenolic compounds, and polysaccharides, play key roles at different stages of the wound-healing process through diverse mechanisms. These studies have categorized the compounds according to their characteristics, bioactivities, and modes of action. In this study, we evaluated the role of natural compounds derived from plant sources that have been shown to play a crucial role in immunomodulation. Macrophages are closely involved in immunomodulation within the wound microenvironment and are key players in efferocytosis, inflammation resolution, and tissue regeneration, all of which contribute to successful wound healing. Phytochemicals and their derivatives have shown capabilities in immune regulation, including macrophage migration, nitric oxide synthase inhibition, lymphocyte and T-cell stimulation, cytokine activation, natural killer cell enhancement, and the regulation of NF-κβ, TNF-α, and apoptosis. In this review, we have studied the role of phytochemicals in immunomodulation for the resolution of diabetic wound inflammation.